Pemberdayaan UMKM Berbahan Dasar Siwalan dalam Menghadapi Era Digitalisasi - Sumriyah Sumriyah; Mufarijul Ikhwan; Ida Wahyuliana; Afrian Wahyu Dewa; Salsabila Rohadi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The siwalan tree, which is a characteristic of Pragaan Daya Village, can be developed into a business that can improve the welfare of residents in the village. So in this way, Village MSMEs can be formed based on siwalan fruits. The implementation of MSMEs must be deceived by improving the quality of business actors and the products they produce in order to get adequate business consistency. In addition, existing MSMEs must prepare themselves for the era of digitalization in running their product businesses by paying attention to technological developments in order to minimize losses due to lagging product development. . This is based on the fact that the ongoing business can keep up with the times, which involves digitalization in all aspects of life, including in the application of siwalan products in Pragaan Daya Village. The purpose of this research is of course so that people in the village can optimize the sophistication of technology to make the digital platform a marketing platform for their products. In addition, of course, to create human resources who can compete in this era of digitalization. So that the initial goal of forming MSMEs can be realized. The empowerment of MSMEs based on siwalan can continue to progress and successfully compete with other MSME products.